KAJIAN HISTORIS-KRITIS TENTANG PENCOBAAN DALAM YAKOBUS 1:12-18 DAN IMPLEMENTASINYA BAGI JEMAAT GMIM SYALOOM TOMPASOBARU DUA - Monding, Yushiko Deasy (Institut Agama Kristen Negeri Manado, 2019)
The purpose of this study is to understand the meaning of temptation in James 1: 12-18 and its implementation for the GMIM Syaloom Tompasobaru Dua Church. This research is a descriptive qualitative research based on observation and interviews. Whereas for text research uses a literary study approach, especially historical criticism. From the results of the text research it is found that James's main advice emphasizes the Jewish Christian community to be happy, rejoice and even become a person who endures trials when facing trials without blaming God with the trials experienced by them . This is similar to what happened at the GMIM Syaloom Tompasobaru Church, which still understands trials not from the positive side.